Network Pharmacology Revealed the Mechanisms of Action of Lithospermum erythrorhizon Sieb on Atopic Dermatitis - Wang T; You W; Zhao L; Zhang B; Wang H (Dove Medical Press, 2023)
Tianyi Wang,1,* Wang You,2,* Linna Zhao,3 Bingxin Zhang,1 Hongmei Wang4 1Department of Dermatology, First Teaching Hospital of Tianjin University of TCM, National Clinical Research Center for Chinese Medicine Acupuncture and Moxibustion, Tianjin, People's Republic of China; 2Department of Internal Medicine, Hexi Hospital of TCM, Tianjin, People's Republic of China; 3Department of Experimental Center, First Teaching Hospital of Tianjin University of TCM, National Clinical Research Center for Chinese Medicine Acupuncture and Moxibustion, Tianjin, People's Republic of China; 4Department of Dermatology, Tianjin Academy of Traditional Chinese Medicine Affiliated Hospital, Tianjin, People's Republic of China*These authors contributed equally to this workCorrespondence: Tianyi Wang, Department of Dermatology, First teaching hospital of Tianjin University of TCM, National Clinical Research Center for Chinese Medicine Acupuncture and Moxibustion, Tianjin, 300300, People's Republic of China, Email tina1989wang@126.comAim: The application of network analysis algorithms promoted the development of network pharmacology. This study aimed to combine network pharmacology and signed random walk with restart (SRWR) to reveal the mechanism by which Lithospermum erythrorhizon Sieb (LES) exerts effects on atopic dermatitis (AD).Methods: The compounds and targets of LES were retrieved from Traditional Chinese Medicine Integrated Database (TCMID) and Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform (TCMSP), and important compounds and targets were identified by intersection analysis and protein-protein interaction (PPI) network.Results: We found that active LES-derived compounds such as caffeic acid, Isovaleric acid, Arnebinol, and Alannan may inhibit PTGS2, HSP90AA1 and MAPK14, which are key mediators involved in PI3K-Akt pathway, vascular endothelial growth factor signaling pathway, Fc epsilon RI signaling pathway, and calcium signaling pathway.Conclusion: The application of SRWR could identify potential targets of LES with a low false-positive rate and help elucidate the mechanism of action of traditional Chinese medicine.Keywords: signed random walk with restart, network pharmacology, Lithospermum erythrorhizon Sieb, atopic dermatitis